2008
DOI: 10.1111/j.1475-1313.2008.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational colour vision requirements for police officers

Abstract: Inclusion of public service professions in the UK Disability Discrimination Act in 2004 prompted a review of occupational colour vision requirements for police officers. Changes in the regulations which existed prior to 2003 were proposed. The aim of this study was to obtain the views of serving police officers in Northern Ireland on the importance of good colour discrimination in everyday police work and on the recruitment regulations for patrol constables introduced in 2003 in mainland UK. These views were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This is in contrast to most standards for policing in other countries, which require normal or near‐normal colour vision . A survey on the Northern Ireland police also showed concerns about safety and ability to perform their job efficiently, such as providing witness statements with these new police standards in the UK …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to most standards for policing in other countries, which require normal or near‐normal colour vision . A survey on the Northern Ireland police also showed concerns about safety and ability to perform their job efficiently, such as providing witness statements with these new police standards in the UK …”
Section: Resultsmentioning
confidence: 99%
“…Occupations differ in their requirement for colour vision and in terms of safety or quality assurance . Furthermore, it appears that no single test, including the Ishihara test, can determine preclusion from a career choice.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of ocular disorders such as refractive errors and particularly color vision defects on occupational life has been a subject to many studies (1)(2)(3)(4)(5)(6)(7). Similar studies were also conducted on medical professionals (8)(9)(10)(11)) and more specifically pathologists or microscopists (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 69%
“…The importance of good color vision was further emphasized by Birch et al [13] in Northern Ireland. They reported that more than 65% of serving police officers considered good color vision important for effective policing with only 2% considering it unimportant.…”
mentioning
confidence: 99%